2002
DOI: 10.1046/j.1529-8027.2002.02026_15.x
|View full text |Cite
|
Sign up to set email alerts
|

Salvage Therapy With Thalidomide In Patients With Advanced Relapsed/Refractory Multiple Myeloma

Abstract: Background and Objectives. Few therapeutic options are presently available for patients with multiple myeloma (MM) who relapse after autologous or allogeneic stem cell transplantation, or for patients who are refractory to conventional chemotherapy and not eligible for salvage high‐dose therapy. Thalidomide, a glutamic acid derivative with anti‐angiogenic properties, has been recently proposed as an effective therapy for patients with advanced refractory disease. The aim of this study was to evaluate the activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
3

Year Published

2003
2003
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 25 publications
6
56
3
Order By: Relevance
“…Remarkable antimyeloma efficacy, reported to be about 30% with thalidomide alone 8,9 and 50% with added dexamethasone 10,11 in advanced and refractory MM, provided the basis for recent clinical trials aimed at investigating the role of these drugs as first-line therapy for patients with symptomatic MM. [12][13][14] The aim of this prospective, multicenter study was to evaluate the efficacy and toxicity of thalidomide and dexamethasone administered as primary therapy in patients with symptomatic MM, and to determine the effect of this combination therapy on stem cell collection and engraftment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkable antimyeloma efficacy, reported to be about 30% with thalidomide alone 8,9 and 50% with added dexamethasone 10,11 in advanced and refractory MM, provided the basis for recent clinical trials aimed at investigating the role of these drugs as first-line therapy for patients with symptomatic MM. [12][13][14] The aim of this prospective, multicenter study was to evaluate the efficacy and toxicity of thalidomide and dexamethasone administered as primary therapy in patients with symptomatic MM, and to determine the effect of this combination therapy on stem cell collection and engraftment.…”
Section: Discussionmentioning
confidence: 99%
“…19 Response rates of about 30% reported by Singhal et al 8 were confirmed by others groups. 9,[20][21][22][23] Addition of dexamethasone to thalidomide in patients who failed to benefit from prior therapy, including both thalidomide and dexamethasone given as single agents, further increased responses, up to an overall response rate of 50-55%. 10,11 These data suggested a synergy between thalidomide and dexamethasone and prompted several groups to explore this combination also in patients with previously untreated MM.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10] One of the most active and promising drugs for this subset of patients is thalidomide, which has provided an overall response rate of around 45%. [11][12][13][14][15][16][17][18] In an attempt to increase this response rate, several groups, including our own, have investigated the efficacy of combining thalidomide with other agents. We designed a protocol (ThaCyDex) that includes thalidomide together with oral cyclophosphamide and dexamethasone.…”
Section: Introductionmentioning
confidence: 99%
“…6 Since then, thalidomide has been widely used as a single agent in heavily pretreated and relapsed or refractory multiple myeloma. [7][8][9][10][11][12][13][14][15][16][17] In vitro studies revealed synergistic activity between dexamethasone (Dex) and thalidomide. 18 Combining thalidomide and Dex in clinical trials clearly represented an advance in treatment options for relapsed MM with overall responses up to 55%.…”
Section: Thalidomidementioning
confidence: 99%